The Effect of L-carnitine supplementation on sportive performance - Eyipinar, C. D. (The Eurasia Proceedings of Health, Environment and Life Sciences, 2023)
L-carnitine is a derivative of two essential amino acids synthesized in the liver and kidneys that our body needs for energy. In the bioenergetics of skeletal muscle, carnitine plays crucial roles. A severe reduction in muscular activity is associated with skeletal muscle carnitine insufficiency. Since L-carnitine supplement is known as a fat burner, its use among athletes has become more common in recent years. This review's objective is to assess the potential mechanistic effects of L-carnitine supplementation on athletic performance. In this context, the literature in the SportDiscus, EMBASE, PubMed and Google Scholar databases was scanned during a 15-year period to gather the data from the publications screened within the scope of SCI, SCI-Expanded, and ESCI. Consequently, it may be argued that taking carnitine supplementation improves athletic performance through a number of processes; including the maintenance of glycogen.